MODELING AND PEER REVIEWING AS SCAFFOLDING IN EFL STUDENTS’ ENGLISH BUSINESS CORRESPONDENCE WRITING - Hartani, Tuti; Sulindra, Eric (Akademi Sekretari Widya Mandala, 2017)
The research aimed to investigate how Modeling and Peer Reviewing as types of scaffoldings in learning, practical expansion of Constructivism approach could assist the EFL (English as Foreign language) learners to improve their writing skill in English Business Correspondence class. As a derivation of Constructivism approach, Modeling and Peer Reviewing, two types of scaffolding in learning (which may employ various teaching methods) tend to put more weight on the social factors of Language Teaching instead of in quest for ‘the best method’. The research methodology used was Classroom Action Research, which utilized the cycles of Action Research: Planning-Acting-Reflecting-Revising the Plan. The data collection was conducted by interviewing, taking learning activity log (field note), and giving Pre-test and Post-test to the student-participants. All these data were analyzed and decoded to see patterns and tendency. The result described that the two scaffolding tools: Modeling and Peer Reviewing were able to give impact to the improvement of students’ English Business Correspondence skills. Modeling and Peer Reviewing generally improved the students’ writing quality and improve their scores. The Modeling action gave initial pictures on the message structure of the business letters, commonly used phrases, writing styles, vocabulary, content/ ideas for writing, grammar and sentence structure. The Peer Reviewing action contributed feedback on the students’ work. The feedback could be upon: grammar and structure, message structure, writing style, diction and set phrases. The recommendation based on the research is that the teachers/lecturers/instructors are to give initial instruction and some explanation regarding the framework or basic concept before applying the Modeling and Peer Reviewing in the classroom. The application of Modeling and Peer Reviewing should also consider: students’ readiness and students’ maturity.